Hormesis and the Salk Polio Vaccine - Edward J. Calabrese Ph.D (SAGE Publishing, 2012)
The production of the Salk vaccine polio virus by monkey kidney cells was generated using the synthetic tissue culture medium, Mixture 199. In this paper's retrospective assessment of this process, it was discovered that Mixture 199 was modified by the addition of ethanol to optimize animal cell survival based on experimentation that revealed a hormetic-like biphasic response relationship. This hormesis-based optimization procedure was then applied to all uses of Mixture 199 and modifications of it, including its application to the Salk polio vaccine during preliminary testing and in its subsequent major societal treatment programs.